Energy Efficient WiFi Display - Zhang, Chi; Zhang, Xinyu; Chandra, Ranveer (ACM MobiSys, 2015)
WiFi Display, also called Miracast, is an emerging technology that allows a mobile device (source) to duplicate its screen content to an external display (sink) via a peer-to-peer WiFi link. Despite its diverse application scenarios and growing popularity, Miracast consumes substantial power due to a combination of video encoding/decoding and transmission. In this paper, we ﬁrst conduct a measurement study to quantify and model key parameters that scale Miracast’s power consumption. We then propose a set of optimization mechanisms to bypass redundant codec operations, reduce video tail trafﬁc, and relocate the Miracast channel dynamically to maximize transmission efﬁciency. We have implemented this energy-efﬁcient Miracast framework on an Android smartphone. Experimental results show that the legacy Miracast system costs 1.3 to 2.4 Watts. Our framework reduces the power consumption by 29% to 61%, depending on the Miracast application’s video trafﬁc patterns. Our optimization mechanisms do not affect the video quality, and can even reduce the latency of certain Miracast applications.